Evaluasi Efektivitas Pembelajaran Aqidah Akhlak : Kajian evaluasi pembelajaran aqidah akhlak melalui Metode ceramah dan diskusi - Najamudin Najamudin (Moral : Jurnal kajian Pendidikan Islam, 2025)
Aqidah Akhlak through a literature review that focuses on lecture and discussion methods. In learning Aqidah Akhlak, choosing the right method is the key to success in delivering material and shaping students' character. The lecture method is effective for delivering basic information systematically, while the discussion method emphasizes more on active student involvement and the development of critical thinking skills. This article reviews various scientific literature to analyze the advantages, disadvantages, and relevance of both methods in learning Aqidah Akhlak. The results of the study show that the use of both methods in an integrated manner can provide more optimal results, with lectures as an introduction and discussions as a deepening of the material. These findings provide a theoretical perspective for educators in designing effective learning strategies.